1983
DOI: 10.1042/bj2100761
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the role of zinc in parturition in the rat

Abstract: 1. Pregnant rats were fed either low (<1 p.p.m.) Zn or control (40p.p.m. Zn) diets from day 10 of gestation. They were killed at intervals during the last 96h preceding the normal time for onset of parturition, and differences in plasma progesterone, oestradiol-17, and ovarian 20a-hydroxysteroid dehydrogenase were assessed. 2. Gestation was prolonged in Zn-deficient rats. 3. Although the preparturient decline in plasma progesterone began at the same time in all groups, at term, plasma progesterone concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Zinc deficiencies in pregnancy for women deprived of animal foods or easily absorbed cereals have risk of babies that are light for their gestational age, for whom poor growth in infancy continues. Zinc deficiency may also be responsible for poor functioning of the human uterus in labour, as is the case for the rat (Bunce et al 1983), albeit experimentally. There is a research opportunity for investigation into this aspect of human labour, taking account of pregnancy diets, maternal nutrition and foetal weights.…”
Section: Zincmentioning
confidence: 96%
“…Zinc deficiencies in pregnancy for women deprived of animal foods or easily absorbed cereals have risk of babies that are light for their gestational age, for whom poor growth in infancy continues. Zinc deficiency may also be responsible for poor functioning of the human uterus in labour, as is the case for the rat (Bunce et al 1983), albeit experimentally. There is a research opportunity for investigation into this aspect of human labour, taking account of pregnancy diets, maternal nutrition and foetal weights.…”
Section: Zincmentioning
confidence: 96%
“…Zinc is important in all biological systems. In vivo and in vitro reproductive studies have shown that zinc is essential for spermatogenesis (Abbasi et al, 1980;Nishi et al, 1984), testosterone production (Leake et al, 1984;Favier, 1992b), as a decapacitation factor (Aonuma et al, 1981;Andrews et al, 1989), for conception (Golub et al, 1984), for blastocyst development and implantation (Hurley & Shrader, 1975;Record et al, 1985;Peters et al, 1991), organogenesis (Hurley (Swenerton, 1966), fetal growth (Prasad et al, 1961;Eriksson, 1984) and parturition (Bunce et al, 1983;Hambridge et al, 1986). The purpose of this study was to investigate the effects of different concentrations of zinc on major components of the bovine IVMFC model.…”
Section: Discussionmentioning
confidence: 99%
“…They were kept alone in makrolon cages on a 12 h light-dark cycle at constant temperature (20-22 ~ and humidity (40-60%) and had free access to food and desionised water. Solid food was a complete maintenance diet from the Usine d'alimentation rationelle, Villemoisson, France (ref: A04), containing 85 mg zinc/kg, and representing for the animals a daily zinc intake of between 1.7 and 2.1 mg, which is considered as adequate [29,30]. Contribution of water to zinc nutriture is negligible.…”
Section: Animals and Dietsmentioning
confidence: 99%